Free‐living, Amphizoic and Opportunistic Amebas - Martinez, Augusto Julio (Brain Pathol, 2008)
Amebas belonging to the genera Naegleria, Acanthamoeba and Balamuthia are free‐living, amphizoic and opportunistic protozoa that are ubiquitous in nature. These amebas are found in soil, water and air samples from all over the world. Human infection due to these amebas involving brain, skin, lung and eyes has increased significantly during the last 10 years. The epidemiology, immunology, protozoology, pathology, and clinical features of the infections produced by these protozoa differ strikingly. Infection by the pathogenic Naegleria fowleri is acquired by exposure to polluted water in ponds, swimming pools and man‐made lakes. Raised temperatures during the hot summer months or warm water from power plants facilitate the growth of N. fowleri. N. fowleri is a thermophilic ameba that grows well in tropical and subtropical climates. The CNS infection, called Primary Amebic Meningoencephalitis (PAM), produced by N. fowleri is characterized by an acute fulminant meningoencephalitis leading to death 3–7 days after exposure. Victims are healthy, young individuals with a history of recent water‐related sport activities. The portal of entry is the olfactory neuroepithelium. The pathologic changes are an acute hemorrhagic necrotizing meningoencephalitis with modest purulent exudate, mainly at the base of the brain, brainstem and cerebellum. Trophozoites can be seen within the CNS lesions located mainly around blood vessels. Thus far 179 cases have been reported; 81 in the USA alone. Balamuthia mandrillaris and several species of Acanthamoeba are pathogenic “opportunistic” free‐living amebas which cause Granulomatous Amebic Encephalitis (GAE) in humans and animals. GAE is an infection, usually seen in debilitated, malnourished individuals, in patients undergoing immunosuppressive therapy for organ transplants and in Acquired Immunodeficiency Syndrome (AIDS). The granulomatous component is negligible, particularly in immunocompromised individuals. Pathologically these amebas produce a patchy, chronic or subacute granulomatous encephalitis with the presence of trophozoites and cysts. The portal of entry is probably through the respiratory tract or an ulceration of the skin reaching the CNS by hematogenous spread. As of October 1, 1996, 166 cases 1103 due to Acanthamoeba and 63 due to Balamothial of GAE have been reported from around the world. Of these 103 cases due to Acanthamoeba (72 have been reported in the USA alone, > 50 in AIDS). It is well known that several species of Acanthamoeba can also produce, chronic sight threatening ulceration of the cornea called Acanthamoeba keratitis (AK), mostly in contact lens wearers or in individuals with minor corneal abrasions. Hundreds of cases of AK have been documented world wide.